Validation of a short Spanish version of the instrument Barriers to Physical Activity Questionnaire for People with Mobility Impairments - Joan Úbeda-Colomer; Carmen Peiró-Velert; José Devís-Devís (Instituto Nacional de Salud Pública, 2018)
Objective. To validate a short Spanish version of the instrument Barriers to Physical Activity Questionnaire for People with Mobility Impairments (BPAQ-MI), applicable to different types of disability. Materials and methods. The questionnaire was administered to 791 university students with disabilities. The factorial structure was validated by confirmatory factor analysis and Spearman correlations were carried out to assess criterion validity. Reliability was assessed using Cronbach's alpha coefficient. Results. The proposed model showed good adjustment indexes and an excellent internal consistency (α= 0.920). Negative relationships emerged between the experienced barriers and time spent in physical activity. Conclusions. The short Spanish version of the BPAQ-MI proves to be a valid and reliable instrument to identify, from a socio-ecological perspective, the barriers to physical activity experienced by students with disabilities. The results provide valuable information to develop programs to promote physical activity in this group.